ChemInform Abstract: An Organocatalytic Domino Michael‐Alkylation Reaction: Highly Enantioselective Construction of Spiro‐Cyclopentanoneoxindoles and Tetronic Acid Scaffolds. Issue 15 (April 2015) - Zhou, Jing; Wang, Qi‐Lin; Peng, Lin; Tian, Fang; Xu, Xiao‐Ying; Wang, Li‐Xin
Abstract: The title reaction of methyleneindolinones with ketoester (II) results in the formation of various spiro‐cyclopentanoneoxindoles which are obtained in high yields, good diastereoselectivities and excellent enantioselectivities via α‐alkylation.